Soil nutrient management influences diversity, community association and functional structure of rhizosphere bacteriome under vegetable crop production - Raimi, Adekunle R.; Ezeokoli, Obinna T.; Adeleke, Rasheed A. (Frontiers in Microbiology, 2023)
Rhizosphere bacterial communities are crucial for plant and soil ecosystem health and productivity and have great potential as key indicators of soil health in agroecosystems. To investigate how they are affected by agronomic practices such as fertiliser application and plant species types, this study analysed the rhizosphere bacterial diversity and functions of vegetable crops cultivated under organic and conventional fertilisers in different farms using highthroughput sequencing of the 16S rRNA gene and co-occurrence network pattern among bacterial species. Overall, rhizosphere bacterial communities varied in response to fertiliser type, with the physicochemical parameters, including NH4, PO4, pH and moisture content largely driving the variations across the farms. Organic farms had a higher diversity richness and more unique amplicon sequence variants than conventional farms. Bacterial community structure in multivariate space was highly differentiated across the farms and between organic and conventional farms. Co-occurrence network patterns showed community segmentation for both farms, with keystone taxa more prevalent in organic than conventional farms. Module hub composition and identity varied, signifying differences in keystone taxa across the farms and positive correlations between changes in microbial composition and ecosystem functions. The organic farms comprised functionally versatile communities characterised by plant growthpromoting keystone genera, such as Agromyces, Bacillus and Nocardioides. The results revealed that organic fertilisers support high functional diversity and stronger interactions within the rhizosphere bacterial community. This study provided useful information about the overall changes in soil microbial dynamics and how the changes influence ecosystem functioning under different soil nutrient management and agronomic practices.